Fake news and education for enlightened citizenry - Claudio Pensieri (Pensa MultiMedia, 2018)
The Fake News' topic is interesting because it is new and it is old at the same time. If we want to define "fake news" we cannot give it a unique meaning. Someone frames fake news only in the social media area, some others extend the meaning to newspapers, someone else to any kind of mass media (TV, Books, Radio, etc.). But it is sure that our students don't know how to detect them and how to fight them. The extent of perceived realism of fake news depends also on the extent of hard-news exposure, with the result that individuals exposed to both hard and fake news find fake-news messages less realistic. So we also need to teach our students how become hard-news reader in order to know and detect fake news. In this article we see the "status" of the Fake News problem, how some national and international laws are going on, and some exercises that we can do with our students in order to be "more democratic".